Delivery of a transforming growth factor β-1 plasmid to mesenchymal stem cells via cationized Pleurotus eryngii polysaccharide nanoparticles - Deng WW (Dove Medical Press, 2012)
Wen Wen Deng*, Xia Cao*, Miao Wang*, Rui Qu, Wei Yan Su, Yan Yang, Ya Wei Wei, Xi Ming Xu, Jiang Nan YuDepartment of Pharmaceutics, School of Pharmacy and Center for Nano Drug/Gene Delivery and Tissue Engineering, Jiangsu University, Zhenjiang, People’s Republic of China*These authors contributed equally to this workAbstract: The objective of this study was to investigate the use of cationized Pleurotus eryngii polysaccharide (CPEPS) as a nonviral gene delivery vehicle to transfer plasmid DNA encoding transforming growth factor beta-1 (pTGF-β1) into mesenchymal stem cells (MSCs) in vitro. Crude P. eryngii polysaccharide was purified, and then cationized by grafting spermine onto the backbone of the polysaccharide. Agarose gel electrophoresis, transmission electron microscopy, and a Nano Sense Zetasizer (Malvern Instruments, Malvern, UK) were used to characterize the CPEPS-pTGF-β1 nanoparticles. The findings of cytotoxicity analysis showed that when the nanoparticles were formulated with a CPEPS/pTGF-β1 weight ratio ≥ 10:1, a greater gel retardation effect was observed during agarose gel electrophoresis. The CPEPS-pTGF-β1 nanoparticles with a weight ratio of 20:1, respectively, possessed an average particle size of 80.8 nm in diameter and a zeta potential of +17.4 ± 0.1 mV. Significantly, these CPEPS-pTGF-β1 nanoparticles showed lower cytotoxicity and higher transfection efficiency than both polyethylenimine (25 kDa) (P = 0.006, Student’s t-test) and LipofectamineTM 2000 (P = 0.002, Student’st-test). Additionally, the messenger RNA expression level of TGF-β1 in MSCs transfected with CPEPS-pTGF-β1 nanoparticles was significantly higher than that of free plasmid DNA-transfected MSCs and slightly elevated compared with that of Lipofectamine 2000-transfected MSCs. Flow cytometry analysis demonstrated that 92.38% of MSCs were arrested in the G1 phase after being transfected with CPEPS-pTGF-β1 nanoparticles, indicating a tendency toward differentiation. In summary, the findings of this study suggest that the CPEPS-pTGF-β1 nanoparticles prepared in this work exhibited excellent transfection efficiency and low toxicity. Therefore, they could be developed into a promising nonviral vector for gene delivery in vitro.Keywords: nonviral gene vector, transfection, plasmid DNA, spermine